Antiretroviral therapy adherence among people living with HIV in Vietnam using a multi-method tool: A cross-sectional study - Ly Trieu Vo; Dung Quoc Phan; Bang Van Khanh Quang; Lan Y Vo; Hanh Thi My Nguyen; Araba Gyan; Han Thi Ngoc Nguyen; Giao Huynh (Asian Pacific Journal of Tropical Medicine)
Objective: To assess antiretroviral therapy (ART) adherence rates and associated factors among people living with HIV in Vietnam. Methods: A cross-sectional study was conducted at the Hospital for Tropical Diseases, Ho Chi Minh City from June to August 2022. Data were collected from 347 people living with HIV using structured questionnaires assessing sociodemographics, substance use, drug side effects, treatment beliefs, treatment satisfaction, and depression. ART adherence was evaluated using a multi-method tool, including selfreport, pill count, the Provider Interview Tool, and the Visual Analog Scale. Participants were classified as having high adherence only if they met all four criteria across these methods. Multivariable logistic regression was used to identify factors influencing adherence, with significance set at P<0.05. Results: High ART adherence was observed in 69.5% of the participants. Adherence was significantly lower among tobacco users (OR 0.49, 95% Cl 0.30-0.83, P=0.007), those with higher depression scores (per 1-point increase) (OR 0.89, 95% Cl 0.84-0.95, P<0.001), frequent substance users (OR 0.50, 95% Cl 0.30-0.83, P=0.007), and those experiencing more severe drug side effects (per level increase) (OR 0.64, 95% Cl 0.45-0.92, P=0.016). Participants able to afford treatment had nearly three times higher odds of adherence than those unable to pay (OR 2.85, 95% Cl 1.48-5.47, P=0.002). Conclusions: ART adherence among people living with HIV in Vietnam remains suboptimal. Interventions should target substance use, drug side effects, financial barriers, and depression screening to improve adherence.